Assessment of Oral Health Status and Treatment Needs in Geriatric Day-care Centers in New Delhi - Mansi Atri; Gurpreet Singh Lamba; Vikas Jeph; N Anup (Wolters Kluwer Medknow Publications, 2024)
Background Poor oral health plagues the elderly all over the world. Many do not recognize the severity of tooth loss, dental caries, and periodontal disease that affect them and do not seek treatment. Objectives To assess the oral health status and treatment needs among the elderly population visiting the old age homes in New Delhi. Materials and Methods A cross-sectional study was conducted among seven purposively selected geriatric day-care centers in New Delhi, and a convenience sample of 518 elderly patients was obtained. The WHO Oral Health Assessment Form 1997 was used to record the clinical findings. Statistical analysis was performed using the Statistical Package for the Social Sciences (SPSS) software version 28, and descriptive results were obtained. Results Four hundred and twenty-eight males (82.6%) and 90 females (17.3%) were examined. The older adults presented high tooth loss with an average of 7 missing teeth, and consequently a high prosthetic need with poor denture hygiene. Most of the older adults were categorized as having "fair" oral hygiene, but almost all respondents presented some degree of periodontal disease. Conclusion The current study highlighted that the majority of the patients reported to be satisfied with their oral health status, but most had periodontal problems followed by an increased need for prosthesis.